Clinical characteristics, HPV involvement, and demographic risk factors in women with cervical intraepithelial neoplasia complicated by vaginal intraepithelial neoplasia - Mindan Xu; Yan Wang (BMC, 2024)
Abstract Purpose This study aimed to explore the clinical characteristics and risk factors associated with cervical intraepithelial neoplasia (CIN) when coexisting with vaginal intraepithelial neoplasia (VAIN). Methods We analyzed the clinical data of 212 patients diagnosed with CIN, including 50 patients with concurrent VAIN. The groups were compared to identify distinct clinical features and independent risk factors for the co-occurrence of CIN and VAIN, using logistic regression analysis. Results Patients with both CIN and VAIN had a median age of 57, significantly older than the 41-year median age of patients with CIN only (P < 0.05). A higher prevalence of HPV infection (98.0%) was observed in the CIN and VAIN group, with a notable rate of multiple HPV infections (67.3%) compared to the CIN-only group (P < 0.05). Educational levels were significantly lower in the combined CIN and VAIN group (P < 0.05). HPV16, 33, and 52 were identified as significant types for single and multiple infections. Multivariate analysis confirmed age as an independent risk factor for CIN with VAIN (P < 0.05). VAIN3 patients were more likely to exhibit HSIL and ASC-H, whereas VAIN1 cases tended to correspond with ASCUS and LSIL diagnoses. Conclusion The co-occurrence of CIN and VAIN is significantly influenced by patient age and educational level. The findings advocate for more diligent vaginal examination during colposcopy in older patients, particularly those with multiple HPV infections and cytological abnormalities, to enhance the early detection of vaginal lesions and prevent missed diagnoses and treatments. Additionally, the high prevalence of HPV infection, especially with certain types, underscores the importance of HPV monitoring in this patient population.